2013
DOI: 10.1093/jac/dks530
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of tigecycline resistance in clinical isolates of Enterobacter cloacae and Enterobacter aerogenes

Abstract: Increased ramA expression due to ramR deregulation is the primary mediator of tigecycline resistance in clinical isolates of E. cloacae and E. aerogenes. However, some ramA-overexpressing isolates do not show changes in ramR, suggesting alternate pathways of ramA regulation; the rarA regulator and the oqxAB efflux pump may also play a role in tigecycline resistance in E. cloacae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Thus, it appeared that, in addition to the AcrAB pump, ECL_01758 and ECL_00054 had tigecycline as the substrate (Table 4). This is of clinical importance for the control of the emergence of tigecycline-resistant strains, since this molecule is increasingly used to fight against MDR Enterobacter (42)(43)(44) Lastly, the plasmid carrying ECL_02124-02125 (annotated as oqxAB genes and transcriptionally induced 743-fold) restored the wild-type phenotype, except for tetracycline, tigecycline, erythromycin, and acridine orange (Tables 3 and 4). The MICs of the fluoroquinolones tested (except moxifloxacin) were even 4-fold higher than those of the wild-type strain (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it appeared that, in addition to the AcrAB pump, ECL_01758 and ECL_00054 had tigecycline as the substrate (Table 4). This is of clinical importance for the control of the emergence of tigecycline-resistant strains, since this molecule is increasingly used to fight against MDR Enterobacter (42)(43)(44) Lastly, the plasmid carrying ECL_02124-02125 (annotated as oqxAB genes and transcriptionally induced 743-fold) restored the wild-type phenotype, except for tetracycline, tigecycline, erythromycin, and acridine orange (Tables 3 and 4). The MICs of the fluoroquinolones tested (except moxifloxacin) were even 4-fold higher than those of the wild-type strain (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Enterobacter spp. develop resistance to tigecycline through AcrAB overproduction (during ciprofloxacin treatment in one study [267]), and this was caused by the overproduction of the RamA regulator (268), although one study concluded that the overexpression of RamA, an not necessarily that of AcrAB, correlated with the resistance, suggesting the involvement of other efflux pumps (269).…”
Section: Enterobacter Aerogenes and Enterobacter Cloacaementioning
confidence: 99%
“…Previous studies have examined TGC resistance mechanism in Enterobacteriaceae (17,18). Reductions in the TGC susceptibility of E. coli laboratory strains and clinical isolates are accompanied by overexpression of AcrAB-TolC; however, these E. coli strains have never exceeded the breakpoint for TGC (Ͼ2 mg/liter) (19,20,27).…”
mentioning
confidence: 99%